2020
DOI: 10.1101/2020.05.11.089524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequential sequestrations increase the incorporation and retention of multiple growth factors in mineralized collagen scaffolds

Abstract: Trauma induced injuries of the mouth, jaw, face, and related structures present unique clinical challenges due to their large size and complex geometry. Growth factor signaling coordinates the behavior of multiple cell types following an injury, and effective coordination of growth factor availability within a biomaterial can be critical for accelerating bone healing. Mineralized collagen scaffolds are a class of degradable biomaterial whose biophysical and compositional parameters can be adjusted to facilitat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…Release of glucose and MGO suggest that soaking already fabricated scaffolds in honey solution was the better method to facilitate release of honey from the scaffold into the surroundings; however, quantifying the total amount of honey released also suggested that even for honey soaked scaffolds, the majority of the honey was retained in the scaffold. These findings were also consistent with prior work to sequester growth factors within the mineralized collagen scaffolds, which also identified a significant fraction was retained within the scaffold [57]. The pH of honey soaked and incorporated scaffolds was also assessed, as mineralized collagen scaffolds have been known to release mineral over time and causing a reduction in pH, with honey also known to have a low pH [30, 60].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Release of glucose and MGO suggest that soaking already fabricated scaffolds in honey solution was the better method to facilitate release of honey from the scaffold into the surroundings; however, quantifying the total amount of honey released also suggested that even for honey soaked scaffolds, the majority of the honey was retained in the scaffold. These findings were also consistent with prior work to sequester growth factors within the mineralized collagen scaffolds, which also identified a significant fraction was retained within the scaffold [57]. The pH of honey soaked and incorporated scaffolds was also assessed, as mineralized collagen scaffolds have been known to release mineral over time and causing a reduction in pH, with honey also known to have a low pH [30, 60].…”
Section: Discussionsupporting
confidence: 84%
“…After sterilization, scaffolds were handled following sterile procedures in a biosafety cabinet. Scaffolds were hydrated following previously described procedures [49, 50, 5357]. Briefly, scaffolds were hydrated in 100% ethanol, then in multiple washes with PBS, and then crosslinked with carbodiimide chemistry in PBS solution:1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC, Sigma-Aldrich) and N-hydroxysuccinimide (NHS, Sigma-Aldrich) at a molar ration of 5:2:1 EDAC:NHS:COOH, with carboxylic acid groups present on the collagen backbone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These meshes do not influence scaffold microarchitecture or negatively affect cell activity in scaffolds and were not included in this study as we focused on modification to scaffold composition. We also reported mineralized collagen scaffolds soaked in media containing soluble biomolecules efficiently sequestered these biomolecules within the scaffold microarchitecture [55], with matrix charge and mineral content suspected to enhance sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that mineralized collagen scaffolds can sequester 60-90% of growth factors from solution [36]. As OPG plays a vital role in osteoclastogenesis inhibition and was found to be released in high levels from both membranes, we subsequently examined OPG release profiles of incorporated and soaked scaffolds comparing results to the conventional mineralized collagen scaffold (MC).…”
Section: Cytokine Analysis Of Amnion and Chorion Derived Matrix Revea...mentioning
confidence: 99%